Digital Jawi Palaeography: Studies from the Perspective of Computer Science - Arbain, Nur Atikah; Azmi, Mohd Sanusi; Muda, Azah Kamilah; Radzid, Amirul Ramzani; Omar, Khairuddin; Emran, Nurul Akmar (Journal of Advanced Computing Technology and Application (JACTA), 2019)
Abstract— Malay artefacts in the form of manuscripts and inscribed stones have high historical values to the Malay civilization, and to the Islamic world. These artefacts contain explicit and implicit information that can unlock ancient information. For example, a manuscript offers explicit information based on the written text, but palaeography study can uncover implicit information, such as who was the author, where did the author came from, the number of authors, date, and the manuscript’s authenticity can also be validated. Palaeography uses the decorations and the type of writings on manuscripts or on inscribed stones as the medium of study. Palaeography experts retrieve information from these mediums by comparing the decorations and type of writings on manuscripts of known origin with manuscripts of unknown origin. The methodology used by palaeography experts is applied in digital palaeography. Digital Jawi palaeography studies types of calligraphy that are on manuscripts, since the Arabic calligraphy has its own history, as much as its birth and development when adopted in certain places. This current study has introduced a new method in the field of image processing based on triangle geometry. This method is based on three key coordinates, which taken from each alphabet. Each alphabet is matched with the model in the Qalam al-Sittah to determine every calligraphy type. This type of calligraphy will become the input to determine palaeography information. Tests were also conducted to determine the validity of the proposed method. Additionally, the Inscribed Stone of Terengganu (IST) was used in preliminary experiments.